HUBUNGAN ANTARA PENGETAHUAN KESELAMATAN SAAT GEMPA DENGAN KEMAMPUAN EVAKUASI DIRI PADA REMAJA DI SMPN 1 PAKEL TULUNGAGUNG - Pria Wahyu Romadhon Girianto; Melani Kartika Sari; Distya Afita Yudyawati (STIKES dan AKZI Karya Husada Kediri, 2023)
Disaster evacuation is a way for people to respond when a disaster occurs and not panic when a disaster occurs but plan what they will do to reduce the number of victims when a disaster occurs. This study aims to determine the relationship between knowledge of safety during an earthquake and the ability to self-evacuate. The research design is correlational analytic with a cross-sectional approach. The population in this study was 224 people, and 67 respondents were chosen with a purposive sampling technique. The independent variable is knowledge about safety during an earthquake, and the dependent variable is the ability to evacuate independently. The measuring instrument uses a questionnaire and data analysis using the Spearman rank test. The results of the study of respondents who are knowledgeable about safety during an earthquake in the good category show that almost half (37.3%) have good self-evacuation abilities. Respondents who are knowledgeable about safety during earthquakes in the moderate category indicate that a small proportion (10.4%) have sufficient self-evacuation capabilities. And respondents who are knowledgeable about safety during an earthquake in the poor category indicate that a small proportion (9%) have sufficient self-evacuation capability. The results of data analysis using the Spearman Rank test showed a significant value of 0.05 (0.018 0.05), so that H1 was accepted, meaning that there was a relationship between knowledge about safety during an earthquake and the ability to self-evacuate. Knowledge of earthquake disasters will make individuals know what they will do and are required to do when facing an earthquake disaster for their personal safety and those around them. It is recommended for students to further increase their knowledge of earthquake disasters so that they can improve their ability to self-evacuate in the face of disasters and reduce casualties.